2011
DOI: 10.2174/092986611795714005
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Chromatin Protamination: An Endocrine Perspective

Abstract: During spermiogenesis, the elongating rat spermatid chromatin undergoes a gradual process of condensation which is initiated in the round spermatids at "step 7" of cytodifferentation in stage VII and extending to elongated spermatids at "step 19" of cytodifferentiation in stage VIII. The mechanism of chromatin condensation in the elongating spermatids is an elaborate process that encompasses several biochemical and biological aspects culminating in the deposition of protamine in DNA grooves. The protamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 141 publications
0
21
0
Order By: Relevance
“…During animal spermiogenesis, mRNA localization and translation are regulated in a stage-specific manner (22)(23)(24). During spermiogenesis, DNA-binding histones are replaced by protamines, resulting in chromatin condensation and cessation of transcription in elongating spermatids (25,26). Hence, in haploid spermatids, transcription and translation are temporally uncoupled to ensure protein synthesis in transcriptionally silent germ cells.…”
Section: A Combination Of Sequences In the 5′ Utr And Coding Region Arementioning
confidence: 99%
“…During animal spermiogenesis, mRNA localization and translation are regulated in a stage-specific manner (22)(23)(24). During spermiogenesis, DNA-binding histones are replaced by protamines, resulting in chromatin condensation and cessation of transcription in elongating spermatids (25,26). Hence, in haploid spermatids, transcription and translation are temporally uncoupled to ensure protein synthesis in transcriptionally silent germ cells.…”
Section: A Combination Of Sequences In the 5′ Utr And Coding Region Arementioning
confidence: 99%
“…Moreover, estrogens, directly or indirectly, affected SPZ chromatin acting on the testis rather than epididymis, since histone-to-protamine exchange takes place during spermiogenesis Overall, our results demonstrated that estrogens, indirectly via stimulatory effects on FSH secretion and/or directly via paracrine actions within the testis, play a key role in spermiogenesis. Interestingly, it is still a matter of debate whether FSH and/or estrogen affect chromatin remodeling in SPT in either a synergistic or an independent way with androgens [42,49,58,71,72]. However, the loss of Cnr1 did not impair fertility [15]: this likely occurs because of mechanisms of SPZ selection (Cnr1 À/À mice produce a sperm with heterogeneous histone content and chromatin quality) and/ or DNA repair operating in the female reproductive tract [73].…”
Section: Estrogens and Spermatid Chromatin Packagingmentioning
confidence: 99%
“…Gonadotropins (LH and FSH) and sex steroids, including androgens and estrogens, were both considered because of their role in male reproduction of vertebrates [34][35][36][37][38][39][40][41][42][43]. LH-stimulated androgen production and action are both necessary for germ cell progression in males.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, core-histones are displaced in their acetylated state [66]. Available reports suggest that the process of histone displacement requires (i) DNA nick/repair induced by topoisomerase which relieves torsional stress associated with histone-to-PRM exchange; (ii) hyperacetylation of histone tails by histone acetyl transferase with a concerted down regulation of histone deacetylase; (iii) histone removal mediated by the recruiting protein BRDT (testis-specific bromodomain protein) able to bind histone acetylated lysines, and (iv) acetylated histone degradation through polyubiquitylation of N-terminal lysines [31]. Histone displacement ends at step 13 SPT [47].…”
Section: Chromatin Reorganization In Sptmentioning
confidence: 99%
“…The main future endpoint will be the characterization of E 2 mechanisms to better understand whether its action is direct and/or mediated. Indeed, it is still a matter of debate whether E 2 and/or FSH affect chromatin remodeling in SPT in either a synergistic or an independent way with androgens [31]. Gene deletion animal models have revealed that both FSH and testosterone levels are implicated in the regulation of chromatin condensation during spermiogenesis [31].…”
Section: Last Considerations and Conclusionmentioning
confidence: 99%